Biomarkers of Environmental Enteric Dysfunction Among Children in Rural Bangladesh. Issue 1 (July 2017) - Campbell, Rebecca K.; Schulze, Kerry J.; Shaikh, Saijuddin; Mehra, Sucheta; Ali, Hasmot; Wu, Lee; Raqib, Rubhana; Baker, Sarah; Labrique, Alain; West, Keith P.; Christian, Parul
ABSTRACT: Objectives: Environmental enteric dysfunction (EED) may inhibit growth and development in low- and middle-income countries, but available assessment methodologies limit its study. In rural Bangladesh, we measured EED using the widely used lactulose mannitol ratio (L:M) test and a panel of intestinal and systemic health biomarkers to evaluate convergence among biomarkers and describe risk factors for EED. Methods: In 539 18-month-old children finishing participation in a randomized food supplementation trial, serum, stool, and urine collected after lactulose and mannitol dosing were analyzed for biomarkers of intestinal absorption, inflammation, permeability and repair, and systemic inflammation. EED scores for each participant were developed using principal component analysis and partial least squares regression. Associations between scores and L:M and with child sociodemographic and health characteristics were evaluated using regression analysis. Results: EED prevalence (L:M > 0.07) was 39.0%; 60% had elevated acute phase proteins (C-reactive protein >5 mg/L or α-1 acid glycoprotein >100 mg/dL). Correlations between intestinal biomarkers were low, with the highest between myeloperoxidase and α-1 antitrypsin ( r  = 0.33, P  < 0.01), and biomarker values did not differ by supplementation history. A 1-factor partial least squares model with L:M as the dependent variable explained only 8.6% of L:M variability. In adjusted models, L:M was associated with child sex and socioeconomic status index, whereas systemic inflammation was predicted mainly by recent illness, not EED. Conclusions: Impaired intestinal health is widespread in this setting of prevalent stunting, but a panel of serum and stool biomarkers demonstrated poor agreement with L:M. Etiologies of intestinal and systemic inflammation are likely numerous and complex in resource-poor settings, underscoring the need for a better case definition with corresponding diagnostic methods to further the study of EED. Abstract : Supplemental Digital Content is available in the text